2007
DOI: 10.22358/jafs/74476/2007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acetylated soyabean peptides on rumen fermentation and nitrogen metabolism in sheep

Abstract: The objective of this study was to determine the effect of acetylated peptides on rumen fermentation and nitrogen metabolism in sheep. Six adult Poll × Dorset crossbred sheep, fi tted with permanent rumen and duodenal fi stulas, were used in a replicated 3 × 3 Latin design experiment. Three basic diets, balanced to similar nitrogen intake, were supplemented with 100 g soyabean meal (SBM), 60 g soyabean peptides (SBP) or 80 g acetylated soyabean peptides (ASP), respectively. The crude protein of soyabean peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Zhang et al 29 found that small peptides had a positive effect on nitrogen retention and the use of protein in goats. In addition, Cao et al 30 reported that, despite digesting greater amounts of nitrogen than those fed SBM, soybean peptide-fed sheep had smaller losses of nitrogen from the feces and urine. However, Wang et al 31 demonstrated a decrease in NDF and ADF digestibility due to infusion of soybean small peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al 29 found that small peptides had a positive effect on nitrogen retention and the use of protein in goats. In addition, Cao et al 30 reported that, despite digesting greater amounts of nitrogen than those fed SBM, soybean peptide-fed sheep had smaller losses of nitrogen from the feces and urine. However, Wang et al 31 demonstrated a decrease in NDF and ADF digestibility due to infusion of soybean small peptides.…”
Section: Discussionmentioning
confidence: 99%
“…The birds were fed a low-nitrogen diet and nitrogen-free diet for one week in trial 2, while they were fed a basal diet and nitrogen-free diet for one week in trial 3. The nitrogen-free diet and low-nitrogen diet (Table S2) were formulated as in previous studies [12,24]. The first three days were the pre-test period and the last four days were the main test period.…”
Section: Birds Diets and Sample Collectionmentioning
confidence: 99%